Developing Pre-Service Teacher Capacity to Make Appropriate Choices of Tasks and Resources through Diagnostic Assessment of Children’s Work - Hurst, Chris (MEGRA Inc, 2014)
This paper reports on one phase of a long-term project investigating mathematical contentknowledge of pre-service teachers. A cohort of second year PSTs conducted a diagnosticassessment and a series of associated tutoring sessions with a primary aged child. The focushere is on the PSTs’ ability to make appropriate task choices following the diagnosticprocess. Results of the study suggest that PSTs are capable of making sound choices oftasks and associated resources based on their mathematical and pedagogical contentknowledge following a targeted diagnostic assessment process.